Resposta :
Resposta e Explicação passo-a-passo:
4(3x + 7) = 3x + 19
12x + 28 = 3x + 19
12x - 3x = 19 - 28
9x = -9
x= -9/9
x = - 1
Resposta:
Solução:
[tex]\sf \displaystyle 4 \cdot (3x + 7) = 3x + 19[/tex]
Aplicando a propriedade distributiva, temos:
[tex]\sf \displaystyle 4\cdot 3x + 4 \cdot 7 = 3x + 19[/tex]
[tex]\sf \displaystyle 12x + 28 = 3x + 19[/tex]
[tex]\sf \displaystyle 12x - 3x = 19 - 28[/tex]
[tex]\sf \displaystyle 9x = - 9[/tex]
[tex]\sf \displaystyle x = -\: \dfrac{9}{9}[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle x =-\:1 }}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
[tex]\sf \boldsymbol{ \sf \displaystyle S = \{ x \in \mathbb{Z} \mid x = -\: 1 \} }[/tex]
Explicação passo-a-passo: